Critical inquiry approach integrated with biology students' experiences effects on analytical thinking skills and empathy - Osacdin, Joycee N.
This study investigated the effects of Critical Inquiry Approach Integrated with Biology Students' Experiences (CASE) on learners' analytical thinking skills and empathy. CASE is a modified teaching approach derived from Critical-Inquiry-Based-Learning and is composed of several stages of learning, including orientation, exploration, analysis, inference, evaluation, and reflection. teaching strategy highlights the use of contradictive information derived from students' relevant experiences to prompt the inquiry process. Students were then encouraged to identify a problem to be solved and formulate a hypothesis based on the contradictive information established. Afterward, a student-led activity and discussion were conducted to explore the problem established and deliberate on the findings to determine how students' previous ideas relate to or are different from their new learnings. A pretest-posttest quasi-experimental research design was used, and 56 Grade 7 students from two intact classes participated in the conduct of the study. One class was exposed to the Critical Inquiry Approach Integrated with Biology Students' Experiences (CASE) and the other to the Conventional Teaching Approach (CTA) during the second grading period of School Year 2020-2021. Due to the public health restrictions caused by' the COVID-19 pandemic, Biology, classes were handled by the researcher online. To test the extent of the effect of the teaching strategies, the Analytical Thinking Skills Test (ATST), Toronto Empathy Questionnaire (TEQ), and Prior Knowledge Test (PKT) were used respectively to measure students' analytical thinking and empathy as well as to evaluate the possible mediating role of prior knowledge in the application of CASE and CTA. The mean pretest and posttest scores of the two groups in the ATST and TEQ were subjected to an independent samples t-test to determine the comparability of these m o classes before and after the intervention. On the other hand, Pearson Product Moment Correlation was used to find out the degree of relationship between analytical thinking and empathy. Lastly, scores obtained by the students in the PKT were considered as a covariate so that ANCOVA could be used to identify if prior knowledge mediates the effects of the teaching approaches on students’ analytical thinking and empathy. Results revealed that although there was significant difference between the mean posttests scores of CASE and CTA in the ATST, students from the CASE group scored higher than the CTA group in all components of analytical thinking. In addition, the CASE group was identified to be significantly better than the CTA group in terms of the matching component of analytical thinking. Meanwhile, the CASE group scored significantly better in the TEQ than the CTA group. The relationship between analytical thinking and empathy was also explored and a significant positive relationship was noted to exist between these two learning outcomes. Lastly, it was determined that prior knowledge did not mediate the effect of CTA and CASE on students’ analytical thinking and empathy. Overall, the study found out the CASE is an effective instructional approach that can be used to foster Biology students’ analytical thinking skills and empathy and has the potential to promote other learning outcomes. Thus, further investigation can be carried out, specifically on utilization in face-to-face classes and its application to improve other components of critical thinking like interpretation, evaluation, inference, explanation, and self-regulation as well as other socio-emotional skills such as confidence and grit.